Household Finances and Social Interaction: Bayesian Analysis of Household Panel Data - Sarah Brown; Pulak Ghosh; Karl Taylor (Institute for the Study of Labor (IZA), 2014)
We investigate the relationship between social interaction and household finances using data from the British Household Panel Survey. We contribute to the existing literature by exploring the relationship between a wide range of aspects of household finances and social interaction, rather than focusing one particular facet of household finances, such as the holding of stocks and shares. To be specific, we develop a Bayesian statistical framework to simultaneously explore both sides of the household balance sheet, i.e. liabilities and assets. Additionally, we allow the influence of social interaction on household finances to be time dependent, which enables us to model the effects of social interaction from a dynamic perspective. We also develop a two-part model to jointly investigate the influence of social interaction on the amount of different types of debt and financial assets held conditional on holding the different types of debt and assets. The analysis suggests that the effect of social interaction is not just restricted to share ownership, with positive effects found for both assets and liabilities. Our analysis also suggests that social interaction is associated with households holding larger amounts of both debt (unsecured and secured) and assets (property and non-housing), even after conditioning on the probability of possessing liabilities and/or assets.
Keywords: D12; D14; C11; 330; assets; debt; household finances; social interaction